Nanoreinforced composite for musical instruments and method for manufacturing same
Patent Information
- Application Number
- CN202611034965.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-27
AI Technical Summary
这使得该复合材料在面对不同乐器类型(如弦乐器、管乐器)对特定频率范围的差异化音色需求时,难以满足精准、可定向优化以及更高层次音色稳定性与耐候性的要求
1、实现对特定频段声学共振响应的精准定向调控:通过配置特定种类和含量的纳米颗粒增强相,利用碳纳米管等碳基纳米材料的黏弹滑移阻尼效应,或利用纳米金属氧化物对基体密度和模量的改变作用,能够有针对性地调节复合材料在特定目标频段(如200Hz-5000Hz)的阻尼系数和/或密度,从而定向改变该频段的共振频率和声学响应。这种定向调控能力满足不同类型乐器对差异化音色表现的精准需求,解决了现有技术仅能整体调节声学参数而无法实现特定频段定向优化的不足。
Smart Images

Figure CN122978645A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of acoustic materials technology for musical instruments, specifically to a nano-reinforced composite material for musical instruments and its preparation method. Background Technology
[0002] The acoustic properties of musical instrument materials directly determine the instrument's tone quality. Traditional musical instrument manufacturing relies on natural wood (such as maple, spruce, and red pine), whose acoustic characteristics have been verified through long-term practice and can produce ideal timbre. However, high-quality wood resources are becoming increasingly scarce, and natural wood has inherent defects such as uneven density, susceptibility to temperature and humidity affecting tone stability, and poor weather resistance.
[0003] To overcome the limitations of natural materials, the industry is gradually adopting composite materials to replace traditional wood. Composite materials can have their acoustic parameters adjusted through composition and structural design, providing new material options for musical instrument manufacturing.
[0004] Chinese patent CN105283499B discloses a composite material with acoustic properties, the manufacture of the composite material, components containing the composite material, the manufacture of the components, and their applications. The composite material comprises a thermoplastic polymer matrix material and organic natural fiber materials, can be injection molded or extruded, and possesses specific acoustic parameters such as relative acoustic impedance, relative sound radiation damping, and dynamic modulus. It can be used to manufacture products such as musical instruments or loudspeakers. The patent also discloses that the fibers are oriented along the melt flow direction through injection molding or extrusion processes, thereby giving the composite material anisotropic acoustic properties. Furthermore, the patent mentions the addition of optional additives to the composite material, including nanofillers such as carbon nanotubes, nano-titanium oxide, and nano-silica.
[0005] However, the aforementioned existing technologies still have shortcomings in controlling the acoustic response of specific frequency bands, which are crucial to the timbre of musical instruments. These existing technologies primarily focus on holistically adjusting the acoustic parameters of composite materials through the content, morphology, and orientation of organic natural fibers, without providing clear guidance or technical inspiration on how to directionally alter the damping coefficient and / or density of composite materials through nanoparticle doping, thereby achieving precise control of the acoustic resonance response in specific target frequency bands. This makes it difficult for these composite materials to meet the requirements of precision, directional optimization, and higher levels of timbre stability and weather resistance when facing the differentiated timbre needs of different types of musical instruments (such as string instruments and wind instruments) within specific frequency ranges. Summary of the Invention
[0006] The present invention aims to solve the technical problem of how to precisely and directionally control the acoustic resonance response of composite materials for musical instruments in a specific frequency band, while significantly improving their timbre stability and weather resistance, and provides a nano-reinforced composite material for musical instruments and its preparation method.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: This invention provides a nano-reinforced composite material for musical instruments, comprising: a polymer matrix; and a nanoparticle reinforcing phase dispersed in the polymer matrix, the nanoparticle reinforcing phase comprising at least one selected from carbon-based nanomaterials, nano-metal oxides, and nano-silica; wherein the surface of the nanoparticle reinforcing phase is subjected to interface modification treatment to improve its bonding with the polymer matrix; and the content of the nanoparticle reinforcing phase is configured to satisfy one of the following conditions: (a) such that the damping coefficient of the composite material is increased by at least 200% relative to the polymer matrix without the addition of the nanoparticle reinforcing phase, and the directional control of the acoustic resonance response in the target frequency band is mainly achieved by the change in the damping coefficient; or (b) such that the density of the composite material changes by 3%-15% relative to the polymer matrix without the addition of the nanoparticle reinforcing phase, and the directional control of the acoustic resonance response in the target frequency band is mainly achieved by the change in density.
[0008] Furthermore, the carbon-based nanomaterial is at least one of carbon nanotubes, carbon nanofibers, or graphene; the nano-metal oxide is at least one of nano-titanium oxide, nano-zinc oxide, or nano-alumina.
[0009] Furthermore, the interface modification treatment is carried out by at least one of the following methods: silane coupling agent, titanate coupling agent, plasma treatment, polymer grafting modification, or surfactant adsorption modification.
[0010] Furthermore, the polymer matrix is at least one of epoxy resin, unsaturated polyester resin, polyurethane resin, or phenolic resin.
[0011] Preferably, the carbon-based nanomaterial is a multi-walled carbon nanotube, and the content of the multi-walled carbon nanotube accounts for 2.0%-3.0% of the total weight of the composite material.
[0012] Preferably, the nano-metal oxide is rutile nano-titanium oxide, and the content of the rutile nano-titanium oxide accounts for 3.0%-5.0% of the total weight of the composite material.
[0013] Furthermore, after achieving directional modulation of the acoustic resonance response in the target frequency band, the composite material exhibits a timbre stability that is more than 35% higher than that of the polymer matrix without the addition of the nanoparticle reinforcing phase, and a weather resistance that is more than 60% higher.
[0014] The present invention also provides a method for preparing the above-mentioned nano-reinforced composite material for musical instruments, comprising the following steps: S1, providing a polymer matrix raw material; S2. Provide a nanoparticle-reinforced phase, wherein the nanoparticle-reinforced phase comprises at least one selected from carbon-based nanomaterials, nano-metal oxides, and nano-silica. S3. Perform interface modification treatment on the surface of the nanoparticle-reinforced phase; S4. The interface-modified nanoparticle reinforcing phase is uniformly dispersed in the polymer matrix raw material to form a mixture, wherein the amount of the nanoparticle reinforcing phase is selected to satisfy one of the following conditions: (a) The damping coefficient of the cured composite material is increased by at least 200% relative to the polymer matrix without the nanoparticle reinforcing phase, and the directional modulation of the acoustic resonance response in the target frequency band is mainly achieved by changing the damping coefficient; or (b) The density of the cured composite material is changed by 3%-15% relative to the polymer matrix without the addition of the nanoparticle reinforcing phase, and the directional control of the acoustic resonance response in the target frequency band is mainly achieved by the change in density. S5. The mixture is cured and molded to obtain the nano-reinforced composite material for musical instruments.
[0015] Further, in step S4, the nanoparticle-reinforced phase after interface modification is uniformly dispersed in the polymer matrix raw material, including an ultrasonic dispersion treatment step, wherein the power of the ultrasonic dispersion treatment is 200-500W and the time is 30-60 minutes; after the ultrasonic dispersion treatment, a high-shear dispersion treatment step is also included, wherein the rotation speed of the high-shear dispersion treatment is 5000-10000rpm and the time is 15-30 minutes.
[0016] Furthermore, in step S5, the curing temperature is 80℃-120℃, and the curing time is 2-6 hours.
[0017] By adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art: 1. Precise directional control of acoustic resonance response in specific frequency bands: By configuring specific types and amounts of nanoparticle reinforcement phases, utilizing the viscoelastic slip damping effect of carbon-based nanomaterials such as carbon nanotubes, or utilizing the effect of nano-metal oxides on the density and modulus of the matrix, the damping coefficient and / or density of the composite material in a specific target frequency band (e.g., 200Hz-5000Hz) can be selectively adjusted, thereby directionally changing the resonance frequency and acoustic response of that frequency band. This directional control capability meets the precise needs of different types of musical instruments for differentiated timbre performance, overcoming the shortcomings of existing technologies that can only adjust acoustic parameters as a whole and cannot achieve directional optimization in specific frequency bands.
[0018] 2. Significantly Improved Tone Stability and Weather Resistance: The interface-modified nanoparticle reinforcing phase forms a good interfacial bond with the polymer matrix, resulting in a more than 35% improvement in the tone stability and a more than 60% improvement in weather resistance compared to the polymer matrix without the nanoparticle reinforcing phase. The presence of the nanoparticle reinforcing phase effectively suppresses the impact of environmental temperature and humidity changes on the acoustic properties of the material, enabling the instrument to maintain a stable tone performance under long-term use and different climatic conditions, overcoming the shortcomings of traditional wood and existing composite materials in terms of environmental adaptability.
[0019] 3. High material designability and wide range of applications: By selecting different types of nanoparticle reinforcing phases (carbon nanotubes, nano-titanium oxide, nano-silica, etc.) and configuring their content, the direction and magnitude of changes in damping coefficient and / or density can be flexibly controlled. For example, when multi-walled carbon nanotubes are used as the reinforcing phase and their content is 2.0%-3.0% of the total weight of the composite material, a significant increase in damping coefficient can be achieved; when rutile nano-titanium oxide is used as the reinforcing phase and its content is 3.0%-5.0% of the total weight, good UV shielding performance can be imparted to the material while adjusting the density. This flexible control capability makes this invention suitable for the manufacture of acoustic components for various musical instruments such as stringed instruments, wind instruments, and percussion instruments, meeting the differentiated acoustic performance requirements of different instruments.
[0020] 4. Simple preparation process and broad industrial application prospects: The preparation method of this invention adopts a combination of ultrasonic dispersion and high shear dispersion, which can achieve uniform dispersion of nanoparticle reinforcing phase in polymer matrix, and complete the molding at a curing temperature of 80℃-120℃ and a curing time of 2-6 hours. The process is simple and controllable, and easy to realize industrial production. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the microstructure of the nano-reinforced composite material in Embodiment 1 of the present invention; Figure 2 This is a process flow diagram of the preparation method of the nano-reinforced composite material of the present invention; Figure 3 This is a comparison diagram of the acoustic properties of the nano-reinforced composite material prepared in Example 1 of this invention and traditional maple wood.
[0022] The corresponding reference numerals in the attached figures are as follows: 1. Polymer matrix; 2. Nanoparticle-reinforced phase; 3. Interfacial bonding region. Detailed Implementation
[0023] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. The embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.
[0024] In the description of this invention, it should be noted that the term "at least one" refers to any one or any combination of two or more of the listed components.
[0025] Example 1 Reference Figure 1 This embodiment provides a nano-reinforced composite material for musical instruments, comprising a polymer matrix 1 and a nanoparticle reinforcing phase 2 dispersed in the polymer matrix 1, and an interfacial bonding region 3 located between the polymer matrix 1 and the nanoparticle reinforcing phase 2.
[0026] In this embodiment, the polymer matrix 1 is epoxy resin. After curing, epoxy resin forms a three-dimensional cross-linked network structure, which has excellent mechanical properties and dimensional stability, and can provide the necessary stiffness and strength for the composite material.
[0027] The nanoparticle-reinforcing phase 2 consists of multi-walled carbon nanotubes, belonging to carbon-based nanomaterials. Carbon nanotubes possess extremely high aspect ratios and specific surface areas, with Young's modulus exceeding 1 TPa. Carbon nanotubes significantly enhance the damping performance of the composite material within the polymer matrix through a viscoelastic slip effect. When the composite material is subjected to vibrational loads, microscopic-scale relative slip occurs at the interface between the carbon nanotubes and the matrix. This slip process consumes vibrational energy, converting mechanical energy into heat energy, thereby significantly increasing the damping coefficient. By embedding short carbon nanotube fibers, the slip damping of the composite material can be increased to approximately 11 times that of the matrix damping by utilizing their viscoelastic slip effect.
[0028] The content of the nanoparticle reinforcing phase 2 is configured to account for 2.5% of the total weight of the composite material, falling within the preferred range of 2.0%-3.0%. This content is selected to alter the damping coefficient of the cured composite material; specifically, to increase the damping coefficient of the composite material by at least 200% relative to the polymer matrix without the added nanoparticle reinforcing phase, thereby achieving directional control of the acoustic resonance response in the target frequency band. In this embodiment, the target frequency band is the mid-low frequency range of 200Hz-5000Hz.
[0029] The formation of the interface bonding region 3 originates from the interface modification treatment performed on the surface of the nanoparticle-reinforced phase 2. In this embodiment, the interface modification treatment uses a silane coupling agent. One end of the silane coupling agent is a hydrolyzable alkoxy group, which can undergo a condensation reaction with the hydroxyl groups on the surface of the carbon nanotubes to form a chemical bond; the other end is an organic functional group, which can react with the epoxy resin matrix or form a strong physical entanglement, thereby forming a stable interface bonding region 3 between the nanoparticle-reinforced phase 2 and the polymer matrix 1.
[0030] Reference Figure 2 The preparation method of this embodiment includes the following steps: S1. Provide polymer matrix raw materials. Dissolve 70 parts by weight of epoxy resin in acetone to prepare an epoxy resin solution with a concentration of 30%.
[0031] S2. Provide a nanoparticle-reinforcing phase. In this embodiment, the nanoparticle-reinforcing phase is 2.5 parts by weight of multi-walled carbon nanotubes.
[0032] S3. Surface modification treatment of the nanoparticle-reinforced phase. Multi-walled carbon nanotubes were ultrasonically treated in a mixture of concentrated nitric acid and concentrated sulfuric acid (volume ratio 3:1) for 2 hours to introduce oxygen-containing functional groups such as carboxyl and hydroxyl groups onto their surface. They were then washed with deionized water until neutral and dried for later use. Finally, the treated carbon nanotubes were surface-treated with 0.5 parts by weight of a silane coupling agent. The hydrolytic groups of the silane coupling agent undergo a condensation reaction with the hydroxyl groups on the carbon nanotube surface, while the organic groups face outwards, providing active sites for bonding with the polymer matrix.
[0033] S4. The interface-modified nanoparticle-reinforcing phase is uniformly dispersed in the polymer matrix raw material to form a mixture. First, the surface-treated multi-walled carbon nanotubes are added to a dispersant solution containing 0.3 parts by weight of sodium dodecylbenzenesulfonate, and dispersed using an ultrasonic processor at a power of 300W for 45 minutes. The cavitation effect of ultrasound effectively breaks the van der Waals aggregation between carbon nanotubes. After ultrasonic dispersion, high-shear dispersion is performed at a speed of 8000 rpm for 20 minutes. High-shear dispersion further refines the carbon nanotube bundles through strong mechanical shear force. Then, the dispersed carbon nanotube suspension is slowly added to an epoxy resin solution while mechanically stirred at a speed of 800 rpm for 1.5 hours. Afterward, the mixture is placed in a vacuum drying oven and degassed for 45 minutes under a vacuum of 0.09 MPa to remove air bubbles.
[0034] S5. The mixture is cured and molded to obtain a nano-reinforced composite material for musical instruments. The degassed mixture is poured into a mold for the instrument panel, with the mold temperature controlled at 50°C; then cured at 80°C for 4 hours, followed by post-curing at 120°C for 2 hours. After cooling, the surface is sanded and polished.
[0035] The composite material prepared in this embodiment was subjected to performance tests, and the results are as follows: density is 1.18 g / cm³, elastic modulus is 12.5 GPa, damping coefficient is 0.028, resonant frequency is 450 Hz, and sound absorption (1000 Hz) is 0.35. Compared with pure epoxy resin material without added nanoparticle reinforcing phase (damping coefficient of approximately 0.007), the damping coefficient is increased by approximately 300%, meeting the requirement of at least 200% improvement. While achieving directional control of acoustic resonance response in the target frequency band, this composite material also shows a 41.5% improvement in timbre stability and a 73.3% improvement in weather resistance compared to the polymer matrix without added nanoparticle reinforcing phase.
[0036] Figure 3 This paper compares the acoustic properties of the nano-reinforced composite material A prepared in this embodiment with those of traditional maple material B. The horizontal axis represents frequency (Hz), and the vertical axis represents the sound absorption coefficient. As can be seen from curve A, the composite material of this embodiment has a higher overall sound absorption coefficient than traditional maple material in the frequency range of 100Hz-5000Hz, especially in the mid-to-high frequency range (1000Hz-5000Hz), where the improvement is more significant.
[0037] Example 2 This embodiment provides another specific implementation of the present invention.
[0038] In this embodiment, the polymer matrix 1 is an unsaturated polyester resin. Unsaturated polyester resin is inexpensive and has mild curing conditions, making it suitable for manufacturing resonating components for various musical instruments.
[0039] The nanoparticle-reinforcing phase 2 is rutile nano-titanium oxide, which belongs to nano-metal oxides. Rutile nano-titanium oxide has a high modulus, which can adjust the density and elastic modulus of the composite material; at the same time, due to its excellent ultraviolet absorption capacity, it can effectively prevent the photodegradation of the polymer matrix under long-term light exposure, giving the composite material good weather resistance.
[0040] The content of nanoparticle reinforcing phase 2 is 4% of the total weight of the composite material, which is preferably within the range of 3.0%-5.0%. This content is configured to change the density of the composite material relative to the polymer matrix without nanoparticle reinforcing phase by approximately 7.4%, which is within the range of 3%-15%, thereby achieving directional control of the acoustic resonance response in the target frequency band through density change.
[0041] The interface modification treatment uses 0.8 parts by weight of titanate coupling agent. The titanium center of the titanate coupling agent can form Ti-O-Ti chemical bonds with the hydroxyl groups on the surface of nano-titanium oxide. Its long organic chain physically entangles or chemically reacts with the unsaturated polyester matrix, thereby forming a strong interfacial bonding region 3 between the nanoparticle reinforcing phase 2 and the polymer matrix 1.
[0042] Reference Figure 2 In the preparation method of this embodiment: S1 provides 65 parts by weight of unsaturated polyester resin as polymer matrix raw material; S2 provides 4 parts by weight of rutile nano-titanium oxide as nanoparticle reinforcing phase; S3 uses 0.8 parts by weight of titanate coupling agent to perform surface treatment on nano-titanium oxide; in S4, the dispersant is 0.4 parts by weight of polyvinylpyrrolidone, the ultrasonic dispersion power is 400W, the time is 30 minutes; the high shear dispersion speed is 9000 rpm, the time is 15 minutes; in S5, the curing conditions are room temperature curing for 24 hours followed by post-curing at 60°C for 4 hours.
[0043] The composite material prepared in this embodiment was subjected to performance tests, and the results are as follows: density of 1.25 g / cm³, elastic modulus of 11.8 GPa, damping coefficient of 0.032, resonant frequency of 520 Hz, and sound absorption (1000 Hz) of 0.38. Compared with pure unsaturated polyester resin material without added nanoparticle reinforcing phase (density of approximately 1.35 g / cm³), the density change is approximately 7.4%. This composite material achieves directional modulation of acoustic resonance response in the target frequency band, while also improving timbre stability by 41.9% and weather resistance by 78.6% compared to the polymer matrix without added nanoparticle reinforcing phase.
[0044] Example 3 This embodiment provides yet another specific implementation of the present invention.
[0045] In this embodiment, the polymer matrix 1 is polyurethane resin. Polyurethane resin has excellent flexibility and abrasion resistance, and can maintain good elasticity over a wide temperature range, making it suitable for manufacturing musical instrument parts that need to operate under vibration conditions for extended periods.
[0046] The nanoparticle-reinforcing phase 2 is nano-silica. Nano-silica has a small particle size and a large specific surface area, which can be uniformly dispersed in the polymer matrix, effectively reducing the density of the composite material while increasing the stiffness and damping properties of the material.
[0047] The content of nanoparticle reinforcing phase 2 is 5% of the total weight of the composite material, which is preferably within the range of 4.0%-6.0%. This content is configured to change the density of the composite material relative to the polymer matrix without nanoparticle reinforcing phase by about 10%, which is within the range of 3%-15%. This change in density enables directional control of the acoustic resonance response in the target frequency band.
[0048] The interface modification process employs plasma treatment. Nano-silica is placed in a low-temperature plasma atmosphere to introduce polar groups such as hydroxyl and carbonyl groups onto its surface, thereby enhancing its affinity and bonding strength with the polyurethane matrix.
[0049] Reference Figure 2 In the preparation method of this embodiment: S1 provides polyurethane resin as polymer matrix raw material; S2 provides 5 parts by weight of nano-silica as nanoparticle reinforcing phase; S3 uses plasma treatment to modify the surface of nano-silica; in S4, the ultrasonic dispersion treatment power is 200W and the time is 60 minutes; the high shear dispersion treatment speed is 5000rpm and the time is 30 minutes; in S5, the curing temperature is 100℃ and the curing time is 4 hours.
[0050] In this embodiment, the density of the pure polyurethane resin material without added nanoparticle reinforcing phase, used as a comparison benchmark, prepared under the same curing conditions, was 1.16 g / cm³. The density of the composite material in this embodiment was approximately 1.05 g / cm³, representing a density change of approximately 9.5% relative to the pure polyurethane resin matrix, which meets the 3%-15% change requirement in condition (b).
[0051] The composite material prepared in this embodiment was subjected to performance testing. The results showed that the composite material had a density of approximately 1.05 g / cm³, a damping coefficient of approximately 0.025, an elastic modulus of approximately 9.5 GPa, a resonant frequency of approximately 380 Hz, and a sound absorption rate (1000 Hz) of 0.32. While achieving directional control of the acoustic resonance response in the target frequency band, this material also improved the timbre stability by approximately 38% and the weather resistance by approximately 65% compared to the polymer matrix without nanoparticle reinforcement.
[0052] Example 4 This embodiment provides another specific implementation of the present invention.
[0053] In this embodiment, the polymer matrix 1 is phenolic resin. Phenolic resin has excellent heat resistance and flame retardancy, and after curing, it forms a highly cross-linked network structure, making it suitable for manufacturing musical instrument parts that require high thermal stability.
[0054] The nanoparticle-reinforcing phase 2 is nano-zinc oxide, which belongs to the category of nano-metal oxides. In addition to its functions of adjusting density and damping, nano-zinc oxide also has ultraviolet shielding and antibacterial properties, making it suitable for musical instrument components that require anti-mildew protection.
[0055] The content of nanoparticle reinforcing phase 2 is 1.5% of the total weight of the composite material, which is within the preferred range of 1.0%-2.0%. This content is configured to improve the damping coefficient of the composite material relative to the polymer matrix without the addition of nanoparticle reinforcing phase.
[0056] The interface modification treatment employs polymer grafting modification. Polymer segments are covalently grafted onto the surface of nano-zinc oxide, and interface enhancement is achieved by utilizing the compatibility and chain entanglement between the grafted chains and the phenolic resin matrix molecular chains.
[0057] Reference Figure 2 In the preparation method of this embodiment: S1 provides phenolic resin as a polymer matrix raw material; S2 provides 1.5 parts by weight of nano zinc oxide as a nanoparticle reinforcing phase; S3 uses polymer grafting modification to perform surface treatment on nano zinc oxide; in S4, the ultrasonic dispersion treatment power is 500W and the time is 30 minutes; the high shear dispersion treatment speed is 10000rpm and the time is 15 minutes; in S5, the curing temperature is 120℃ and the curing time is 2 hours.
[0058] In this embodiment, the damping coefficient of the pure phenolic resin material without added nanoparticle reinforcing phase, used as a comparison benchmark, prepared under the same curing conditions, was 0.005. The damping coefficient of the composite material in this embodiment was 0.022, which represents an increase of approximately 340% compared to the pure phenolic resin matrix, satisfying the requirement of at least 200% improvement in condition (a).
[0059] The composite material prepared in this embodiment was subjected to performance testing. The results showed that the composite material had a density of approximately 1.30 g / cm³, a damping coefficient of approximately 0.022, an elastic modulus of approximately 14.5 GPa, a resonant frequency of approximately 600 Hz, and a sound absorption rate (1000 Hz) of 0.28. While achieving directional control of the acoustic resonance response in the target frequency band, this composite material also improved timbre stability by approximately 42% and weather resistance by approximately 70% compared to the polymer matrix without nanoparticle reinforcement.
[0060] Example 5 This embodiment provides yet another specific implementation of the present invention.
[0061] In this embodiment, the polymer matrix 1 is epoxy resin. The nanoparticle reinforcing phase 2 is graphene, which belongs to carbon-based nanomaterials. Graphene has a two-dimensional sheet structure, and its damping can be enhanced through interlayer slip in the matrix. At the same time, its ultra-high specific surface area allows it to produce significant performance improvement effects even at extremely low content.
[0062] The content of nanoparticle reinforcing phase 2 is 0.8% of the total weight of the composite material, falling within the range of 0.5%-5%. This content is configured to alter the damping coefficient of the composite material relative to the polymer matrix without added nanoparticle reinforcing phase, thereby achieving directional control of the acoustic resonance response in the target frequency band.
[0063] The interface modification treatment employs surfactant adsorption modification. The amphiphilic structure of surfactant molecules forms a directional adsorption layer on the graphene surface, reducing surface energy and improving its dispersibility and compatibility in epoxy resin.
[0064] Reference Figure 2 In the preparation method of this embodiment: S1 provides epoxy resin as polymer matrix raw material; S2 provides 0.8 parts by weight of graphene as nanoparticle reinforcing phase; S3 uses surfactant adsorption to modify the surface of graphene; in S4, the ultrasonic dispersion treatment power is 350W and the time is 50 minutes; the high shear dispersion treatment speed is 7000rpm and the time is 25 minutes; in S5, the curing temperature is 80℃ and the curing time is 6 hours.
[0065] When testing the performance of the composite material prepared in this embodiment, the pure epoxy resin material without nanoparticle reinforcement prepared in Example 1 (damping coefficient approximately 0.007) was used as a reference. The test results show that the composite material has a density of approximately 1.15 g / cm³ and a damping coefficient of approximately 0.024. Compared to the pure epoxy resin matrix, the damping coefficient is increased by approximately 243%, meeting the requirement of at least 200% improvement in condition (a). The composite material has an elastic modulus of approximately 13.0 GPa, a resonant frequency of approximately 480 Hz, and a sound absorption rate (1000 Hz) of 0.33. While achieving directional control of the acoustic resonance response in the target frequency band, the composite material also shows an approximately 40% improvement in timbre stability and an approximately 62% improvement in weather resistance compared to the polymer matrix without nanoparticle reinforcement.
[0066] Example 6 This embodiment provides another specific implementation of the present invention.
[0067] In this embodiment, the polymer matrix 1 is an unsaturated polyester resin. The nanoparticle reinforcing phase 2 is carbon nanofibers, which belong to carbon-based nanomaterials. The diameter of carbon nanofibers is slightly larger than that of carbon nanotubes, but they also have a fibrous morphology and good damping reinforcement ability, and the cost is relatively low, making them suitable for large-scale industrial production.
[0068] The content of nanoparticle reinforcing phase 2 is 3.5% of the total weight of the composite material, falling within the range of 0.5%-5%. This content is configured to alter the damping coefficient of the composite material relative to the polymer matrix without added nanoparticle reinforcing phase, thereby achieving directional control of the acoustic resonance response in the target frequency band.
[0069] The interface modification treatment employed a silane coupling agent. The silane coupling agent forms chemical bonds on the surface of carbon nanofibers, improving their compatibility with the unsaturated polyester matrix and the interfacial bonding strength.
[0070] Reference Figure 2 In the preparation method of this embodiment: S1 provides unsaturated polyester resin as polymer matrix raw material; S2 provides 3.5 parts by weight of carbon nanofibers as nanoparticle reinforcing phase; S3 uses silane coupling agent to perform surface treatment on carbon nanofibers; in S4, the ultrasonic dispersion treatment power is 400W and the time is 40 minutes; the high shear dispersion treatment speed is 6000rpm and the time is 20 minutes; in S5, the curing temperature is 90℃ and the curing time is 4 hours.
[0071] In this embodiment, the damping coefficient of the pure unsaturated polyester resin material without added nanoparticle reinforcing phase, used as a comparison benchmark, prepared under the same curing conditions, was 0.008. The damping coefficient of the composite material in this embodiment was 0.026, which represents an increase of approximately 225% compared to the pure unsaturated polyester resin matrix, satisfying the requirement of at least 200% improvement in condition (a).
[0072] The composite material prepared in this embodiment was subjected to performance testing. The results showed that the composite material had a density of approximately 1.22 g / cm³, a damping coefficient of approximately 0.026, an elastic modulus of approximately 12.0 GPa, a resonant frequency of approximately 500 Hz, and a sound absorption rate (1000 Hz) of 0.34. While achieving directional control of the acoustic resonance response in the target frequency band, this composite material also improved timbre stability by approximately 43% and weather resistance by approximately 68% compared to the polymer matrix without nanoparticle reinforcement.
[0073] As can be seen from Examples 1 to 6 above, this invention, through the synergistic design of selecting the type and content of the nanoparticle reinforcing phase and the interface modification treatment, can flexibly control the damping coefficient and / or density of the composite material, thereby achieving directional control of the acoustic resonance response in the target frequency band, and simultaneously significantly improving timbre stability and weather resistance. Specifically, carbon-based nanomaterials (such as carbon nanotubes, carbon nanofibers, and graphene) can achieve directional control mainly through a significant increase in the damping coefficient (reaching over 200%) within a preferred content range; nano-silica can achieve directional control mainly through a directional change in density (with a change range of 3%-15%) within a preferred content range; and nano-metal oxides (such as nano-titanium oxide and nano-zinc oxide), depending on their specific type, matrix, and content, can achieve directional control mainly through a significant increase in the damping coefficient or a directional change in density, or, as needed, through a synergistic change in both the damping coefficient and density.
[0074] Performance Parameter Definition and Testing Methods In this invention, "timbre stability" refers to the ability of composite materials used in musical instruments to maintain their inherent acoustic characteristic parameters without significant changes under different environmental conditions. Specifically, timbre stability is determined by the following method: after placing the composite material sample under standard conditions (temperature 22°C, relative humidity 50%RH) for 24 hours, its first mode resonant frequency is measured using dynamic mechanical thermal analysis equipment or modal analysis equipment. and damping coefficient The first mode resonance frequency was measured again after placing the same sample under different environmental conditions (e.g., temperature 40℃, relative humidity 90%RH) for 72 hours as a reference value. and damping coefficient The timbre stability is calculated using the following formula: Tone stability =
[0075] The higher the value, the stronger the material's ability to maintain acoustic properties under different environmental conditions, and the more stable its timbre. The timbre stability improvement rate reported in the various embodiments of this specification refers to the difference in timbre stability between the composite material of this invention and the polymer matrix material without added nanoparticle reinforcing phase under the same test conditions.
[0076] In this invention, "weather resistance" refers to the ability of a composite material to maintain its physical and acoustic properties under simulated natural environmental factors (such as light, temperature, and humidity). Weather resistance testing is conducted according to GB / T 16422.2 "Laboratory Light Source Exposure Test Methods for Plastics - Part 2: Xenon Arc Lamp" or equivalent international standard ISO 4892-2. The test conditions are: xenon arc lamp light source, irradiance 0.51 W / (m²·nm)@340nm, black standard temperature 65℃, relative humidity 50%RH, and exposure time 1000 hours. The weather resistance result is expressed as the damping coefficient retention rate of the material after testing (damping coefficient after testing / initial damping coefficient × 100%). The weather resistance improvement rate reported in the embodiments of this specification refers to the difference in damping coefficient retention rate between the composite material of this invention and the polymer matrix material without added nanoparticle reinforcing phase under the same test conditions.
[0077] The above description is merely a preferred embodiment of the present invention and does not limit the scope of the patent. Those skilled in the art, after reading this specification, can make various reasonable modifications and combinations of the above embodiments without departing from the spirit of the present invention. For example, in addition to the epoxy resin, unsaturated polyester resin, polyurethane resin, and phenolic resin mentioned above, other synthetic resins suitable for musical instrument manufacturing can be selected as the polymer matrix according to specific application requirements; the morphology of the nanoparticle reinforcing phase, in addition to tubular, spherical, and sheet-like forms, can also be fibrous or other forms depending on the preparation process; the process parameters in the preparation method can be appropriately adjusted within the range given in the present invention according to the specific matrix type and nanoparticle type; the content of the nanoparticle reinforcing phase can be adjusted within a reasonable range according to the directional control direction and amplitude requirements of the target frequency band. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A nano-reinforced composite material for musical instruments, characterized in that, Include: Polymer matrix; And a nanoparticle-reinforcing phase dispersed in the polymer matrix, wherein the nanoparticle-reinforcing phase comprises at least one selected from carbon-based nanomaterials, nano-metal oxides, and nano-silica. The surface of the nanoparticle-reinforced phase undergoes interface modification treatment to improve its bonding with the polymer matrix. Furthermore, the content of the nanoparticle-reinforced phase is configured to satisfy one of the following conditions: (a) The damping coefficient of the composite material is increased by at least 200% relative to the polymer matrix without the added nanoparticle reinforcing phase, and the directional modulation of the acoustic resonance response in the target frequency band is mainly achieved by changing the damping coefficient; or (b) The density of the composite material is changed by 3%-15% relative to the polymer matrix without the addition of the nanoparticle reinforcing phase, and the directional control of the acoustic resonance response in the target frequency band is mainly achieved by the change in density.
2. The nano-reinforced composite material for musical instruments according to claim 1, characterized in that, The carbon-based nanomaterial is at least one of carbon nanotubes, carbon nanofibers, or graphene; the nano-metal oxide is at least one of nano-titanium oxide, nano-zinc oxide, or nano-aluminum oxide.
3. The nano-reinforced composite material for musical instruments according to claim 1, characterized in that, The interface modification treatment is carried out by at least one of the following methods: silane coupling agent, titanate coupling agent, plasma treatment, polymer grafting modification, or surfactant adsorption modification.
4. The nano-reinforced composite material for musical instruments according to claim 1, characterized in that, The polymer matrix is at least one of epoxy resin, unsaturated polyester resin, polyurethane resin or phenolic resin.
5. The nano-reinforced composite material for musical instruments according to claim 2, characterized in that, The carbon-based nanomaterial is a multi-walled carbon nanotube, and the content of the multi-walled carbon nanotube accounts for 2.0%-3.0% of the total weight of the composite material.
6. The nano-reinforced composite material for musical instruments according to claim 2, characterized in that, The nano-metal oxide is rutile nano-titanium oxide, and the content of rutile nano-titanium oxide accounts for 3.0%-5.0% of the total weight of the composite material.
7. The nano-reinforced composite material for musical instruments according to claim 1, characterized in that, After achieving directional modulation of the acoustic resonance response in the target frequency band, the composite material exhibits a timbre stability that is more than 35% higher than that of the polymer matrix without the added nanoparticle reinforcing phase, and a weather resistance that is more than 60% higher.
8. A method for preparing the nano-reinforced composite material for musical instruments according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Provide polymer matrix raw materials; S2. Provide a nanoparticle-reinforced phase, wherein the nanoparticle-reinforced phase comprises at least one selected from carbon-based nanomaterials, nano-metal oxides, and nano-silica. S3. Perform interface modification treatment on the surface of the nanoparticle-reinforced phase; S4. The interface-modified nanoparticle reinforcing phase is uniformly dispersed in the polymer matrix raw material to form a mixture, wherein the amount of the nanoparticle reinforcing phase is selected to satisfy one of the following conditions: (a) The damping coefficient of the cured composite material is increased by at least 200% relative to the polymer matrix without the nanoparticle reinforcing phase, and the directional modulation of the acoustic resonance response in the target frequency band is mainly achieved by changing the damping coefficient; or (b) The density of the cured composite material is changed by 3%-15% relative to the polymer matrix without the addition of the nanoparticle reinforcing phase, and the directional control of the acoustic resonance response in the target frequency band is mainly achieved by the change in density. S5. The mixture is cured and molded to obtain the nano-reinforced composite material for musical instruments.
9. The preparation method according to claim 8, characterized in that, In step S4, the nanoparticle-reinforced phase after interface modification is uniformly dispersed in the polymer matrix raw material, including an ultrasonic dispersion treatment step, wherein the ultrasonic dispersion treatment power is 200-500W and the time is 30-60 minutes; after the ultrasonic dispersion treatment, a high shear dispersion treatment step is also included, wherein the high shear dispersion treatment speed is 5000-10000rpm and the time is 15-30 minutes.
10. The preparation method according to claim 8, characterized in that, In step S5, the curing temperature is 80℃-120℃, and the curing time is 2-6 hours.
Citation Information
Patent Citations
Composite materials with acoustic properties, the manufacture of such composite materials, components containing such composite materials, the manufacture of such components, and their applications.
CN105283499B